C-N vs. C-C Bond Photodissociation in N-(tert-butyldiphenylmethyl)aniline - Stylianos Garas; Michael G. Siskos; Antonios K. Zarkadis (International Journal of Photoenergy)
The direct photolysis of the title aniline compound Ph2(Me3C) C-NHPh in acetonitrile with 248 nm laser light results in the dissociation of the C-N bond giving the corresponding (tert-Bu)diphenylmethyl radical 1a• and the anilino radical PhNH• detectable by ns-laser flash photolysis (LFP) and ESR spectroscopy. The same radical 1a• is also produced from the corresponding (tert-Bu)diphenylmethyl chloride Ph2(Me3C)C-Cl either photolytically in MeCN through C-Cl bond homolysis or pulse radiolytically in THF; the (tert-Bu)diphenylmethyl cation is also detected, however, at sorter time scales because of its high reactivity in the solvent MeCN. At higher laser pulse intensities the radical 1a• is reexcited by a second photon leading through electrocyclization to the 4a,4b-dihydro-9-tert-butylfluorenyl radical (DHBF•) and finally to fluorenyl products. Product analyses of steady state photolyses using GC and GC-MS gave as principal products (tert-Bu)diphenylmethane, aniline and various 9-substituted fluorenyl derivatives, corroborating further the primary C-N bond cleavage and the formation of the radicals 1a• and PhNH•. Other conceivable dissociation pathways leading to the C-CMe3 or N-H bond rupture were not observed.